GSDMD-mediated mitochondrial dysfunction in marginal cells: A potential driver of inflammation and stria vascularis damage in CIHL - Yu Xiao; Xiaohan Zhang; Siwei Guo; Ziyi Liu; Xiaoxu Zhao; Fengyue Dong; Xiuli Bi; Guodong Hong; Miao Chang; Ruifeng Qiao; Shengda Cao; Ying Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Inflammation is among the known causes of cisplatin-induced hearing loss (CIHL), but its exact pathophysiological mechanisms remain unclear. Herein, we demonstrated that pyroptosis—a recently identified inflammatory type of regulated cell death dependent on gasdermin D (GSDMD)—was activated in the cochleae of cisplatin-treated mice, causing CIHL. Meanwhile, treatment with the GSDMD inhibitor necrosulfonamide alleviated CIHL in these mice. To further examine the role of GSDMD-mediated pyroptosis in CIHL, we conducted experiments in Gsdmd- deficient mice . Gsdmd −/− mice demonstrated significantly lower cisplatin-induced cochlear damage than control mice and appeared to be invulnerable to CIHL. Furthermore, GSDMD-mediated pyroptosis in the stria vascularis (SV), but not in the hair cells (HCs), played a dominant role in CIHL. In marginal cells (MCs) of SV, cisplatin induced caspase-dependent GSDMD cleavage, and the pore-forming N-terminal of GSDMD rapidly localized to the mitochondria, leading to abnormal mitochondrial aggregation and oxidative stress. The consequent mitochondrial dysfunction in MCs might result in the severe progression of inflammation, SV damage, and HC loss. Notably, the pharmacological inhibition of pyroptosis using the FDA-approved drug disulfiram effectively alleviated the symptoms of CIHL. Collectively, these findings offer a broad avenue for inhibiting pyroptosis-induced cisplatin ototoxicity and provide valuable theoretical insights for the clinical management of CIHL.